TRANSLATION TECHNIQUES OF ANAK NA DANGOL NI ANDUNG: MANDAILING FOLKLORE INTO ENGLISH - Zainuddin Hasibuan; Syahron Lubis; Amrin Saragih; Muhizar Muchtar (AICLL: ANNUAL INTERNATIONAL CONFERENCE ON LANGUAGE AND LITERATURE, 2018)
This study is about how to formulate the translation technique applied by the translator in translating Mandailing Folklore Anak Na Dangol Ni Andung into English, to identify the translation technique used in translating Anak Na Dangol Ni Andung into English, and to know the quality of translation in translating Anak Na Dangol Ni Andung into English. The purpose of this study were to (1) formulate the translation technique that was applied by the translator in translating Mandailing Folklore Anak Na Dangol Ni Andung into English, (2) identify the translation technique that was used in translating Anak Na Dangol Ni Andung into English, and (3) know how the quality of translation in translating Anak Na Dangol Ni Andung into English. The research findings are as follows. First, this study found that in translating the text Anak Na Dangol Ni Andung into English discovered the existence of two techniques, namely single translation technique 9,1% and dual translation technique 90,9%. Second, the results showed that from 22 data consists of 50% data is an accurate translation and 50% less accurate translation. Meanwhile, 77.3% were acceptable and 22.7% less acceptable. From the aspect of its readability, 86.4% had high readability and 13.6% had medium readability. From the results of this research of 22 data sources analyzed, it was identified that the quality of the translation is accurate, acceptable and has a high degree of readability.